(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Upper cross syndrome refers to a particular configuration of overlapping overactive and underactive muscle groups in the neck, chest and shoulders. Typically, poor posture causes the syndrome, including the forward head posture, which occurs when people use electronic devices, read, and drive. The present study is intended to investigate the effect of kinesio taping on upper cross syndrome Objectives: 1. To study the effectiveness of kinesio taping, Hot Moist Pack and exercises in upper cross syndrome, 2. To study the effectiveness of IFT, HMP and exercises in upper cross syndrome and 3. To compare the effectiveness of kinesio taping and IFT in upper cross syndrome. Methodology: The study consisted of 2 groups. Group A was experimental group and Group B was conventional group. Both the groups received treatment protocol for 2 weeks. Sample size was 60 with 30 in each group. Results: Visual analogue scale, cranio-vertebral angle and forward shoulder angle were used as outcome measures. Statistically significant results were found with VAS p=<0.0001, cranio-vertebral angle p=0.0632 and forward shoulder angle p=0.285 Conclusion: The study concluded that the use of kinesio taping is recommended in reducing pain and improving the neck angles in participants with upper cross syndrome as compared to conventional therapy.